Experimental study of the edgewise compressive mechanical properties of biomimetic fully integrated honeycomb plates. (November 2019) - Tuo, Wanyong; Wei, Peixing; Chen, Jinxiang; Okabe, Yoji; Zhang, Xiaoming; Xu, Mengye
In the present study, the edgewise compressive mechanical properties of the biomimetic fully integrated honeycomb plates manufactured from short basalt fiber reinforced polymer are studied. The findings are as follows: (1) Fully integrated honeycomb plates are primarily characterized by compression failure of the non-perforated surface when bearing an edgewise compressive load. The fully integrated honeycomb plates clearly exhibit the features of plasticity. (2) A buckling failure mode of the upper or lower laminates is not observed in the fully integrated honeycomb plates, and the fully integrated honeycomb plates possess the ideal integrity. Additionally, the fully integrated honeycomb plates produced with 9-mm-long fibers have the greater shearing modulus of elasticity and good plastic deformation ability. These results are of significance for disaster prevention and safety in quakeproof applications. (3) The failure features, mechanical property parameters, and simple calculation formula for edgewise compression of fully integrated honeycomb plates obtained in this work provide a foundation for the prediction of edgewise compression and the design of fully integrated honeycomb plates in future engineering applications.